Pertumbuhan semai Alstonia scholaris, Acacia auriculiformis dan Muntingia calabura yang diinokulasi fungi mikoriza arbuskula pada media tanah bekas tambang kapur - Retno Prayudyaningsih (Jurnal Penelitian Kehutanan Wallacea, 2014)
The application of Arbuscular Mycorrhizal Fungi (AMF) is a solution to produce high quality seedlings. Seedlings inoculated by AMF has high survival rate, especially on extreme land condition such as post mining limestone. Alstonia scholaris, Acacia auriculiformis and Muntingia calabura are tolerant plants species to alkaline and poor soils such as post mining limestone. The research was conducted to determine the effect of inoculation of indigenous AMF from post mining limestone on the seedling growth A. scholaris, A. auriculiformis and M. calabura. A complete randomized design with five treatments of AMF types (Acaulospora sp., Gigaspora sp., mix of Acaulospora sp. and Gigaspora sp., Glomus sp. and non AMF inoculation) was applied. The results showed that inoculated seedlings with indigenous AMF had higher growth response than non inoculated seedlings of A. scholaris, A. auriculiformis and M. calabura. Indigenous AMF inoculation improved height and stem diameter growth, biomass and quality index of seedlings as well as P uptake. The best increment growth is shown by A. auriculiformis seedling after inoculating with Acaulospora sp. and mix of Acaulospora sp. and Gigaspora sp, while inoculation with Acaulospora sp. gave the best increment on seedling growth of A. scholaris and M. calabura.